Comparative Approach to Define Increased Regulatory T Cells in Different Cancer Subtypes by Combined Assessment of CD127 and FOXP3 - Marc Beyer; Sabine Classen; Elmar Endl; Matthias Kochanek; Martin R. Weihrauch; Svenja Debey-Pascher; Percy A. Knolle; Joachim L. Schultze (Clinical and Developmental Immunology)
In recent years an increase of functional CD4+CD25+ regulatory T cells (Treg cells) has been established for patients with solid tumors, acute leukemias, and lymphomas. We have reported an expanded pool of CD4+CD25high Treg cells in patients with chronic lymphatic leukemia (CLL), multiple myeloma (MM) as well as its premalignant precursor monoclonal gammopathy of undetermined significance (MGUS). In healthy individuals, low-level expression of CD127 on T cells in addition to the expression of FOXP3 has been associated with Treg cells. Here, we demonstrate that the expanded FOXP3+ T-cell population in patients with colorectal cancer, CLL, MGUS, MM, follicular lymphoma, and Hodgkin's disease are exclusively CD127low Treg cells and were strongly suppressive. A significant portion of CD127lowFOXP3+ Treg cells expressed only low levels of CD25 suggesting that the previously reported expansion of CD25+ Treg cells underestimates the true expansion. The assessment of CCR7 and CD45RA expression on the expanded CD4+CD127lowFOXP3+ Treg cells revealed an increase of both naïve as well as central and effector memory Treg cells in peripheral blood. Our data strongly support superiority of combined CD127 and FOXP3 analysis in comparison to CD25 and FOXP3 assessment for further quantification of Treg cells in malignant diseases.